Modelling of Sunshine Duration for Peninsular Malaysia - Win, Maw Hlaing Oo (1997)
Knowledge of solar radiation at any area is important for designing solar energy conversion systems, and is also useful for ecophysiological studies. In the present study, we have analysed the daily sunshine duration records for Peninsular Malaysia and apply them in solar radiation modelling. Firstly, we fitted Angstrom type equation to solar radiation and sunshine duration, to deter mine the relation between them. We have found that the seasonal variations of the regression parameters, are different for even two nearby locations. Variation of solar radiation within a small area are also noticable. Secondly, we have studied on the probability distribution nature of daily relative sunshine duration. Daily relative sunshine duration data are fitted to three models. Parameters of the models are estimated only from the monthly mean. Kolmogorov-Smirnov test is applied to determine the goodness of fit. We have found that the four stations can model led by two distributions. Data are also fitted to well known beta distribution model. The effect of variance is also presented. Finally, time series analysis of daily relative sunshine duration data are presented in chapter 4. Using gaussian mapping technique, nonstationary and non-normal distribution nature of the sunshine can be transformed into stationary and normal distribution. The autocorrelation function and partial autocorrelation function show the characteristics of autoregressive process. Results from the Box-Pierce and Ljung-Box statistics indicate that the first order autoregressive model is not suitable, while the second order autoregressive model gives satisfactory results. The relative sunshine duration of any day is dependent on the previous two days.